2015
DOI: 10.1038/cdd.2015.133
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage-induced ephrin-B2 reverse signaling promotes chemoresistance and drives EMT in colorectal carcinoma harboring mutant p53

Abstract: Mutation in the TP53 gene positively correlates with increased incidence of chemoresistance in different cancers. In this study, we investigated the mechanism of chemoresistance and epithelial-to-mesenchymal transition (EMT) in colorectal cancer involving the gain-of-function (GOF) mutant p53/ephrin-B2 signaling axis. Bioinformatic analysis of the NCI-60 data set and subsequent hub prediction identified EFNB2 as a possible GOF mutant p53 target gene, responsible for chemoresistance. We show that the mutant p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 51 publications
2
78
0
Order By: Relevance
“…Loss or mutation of the p53 gene has been identified to be positively associated with the recurrent incidence of chemotherapeutic resistance in different types of cancer (27). In CRC, p53 is mutated in ~50% of patients and these mutations of are considered to be inactivating, leaving to TP53 being incapable of regularly exerting its functions, including its pro-apoptotic role (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Loss or mutation of the p53 gene has been identified to be positively associated with the recurrent incidence of chemotherapeutic resistance in different types of cancer (27). In CRC, p53 is mutated in ~50% of patients and these mutations of are considered to be inactivating, leaving to TP53 being incapable of regularly exerting its functions, including its pro-apoptotic role (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor metastasis is a complex process, and is highly regulated by multiple mechanisms, including aberrant activation of the phosphoinositide 3-kinase (PI3K)/AKT and transforming growth factor (TGF)-β/Smad pathways (8)(9)(10)(11). Furthermore, a large number of studies have shown that matrix metalloproteinase (MMP) overexpression is involved in numerous malignant tumors, including esophageal cancer, breast cancer, liver cancer and rectal cancer (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The growing description of biochemical and biological functions of mutant p53 shows that it not only loses the tumor-suppressive functions of its wildtype counterpart but also acquires novel oncogenic gain-offunction (GOF) properties (12). It has been previously demonstrated that mutant p53 interacts with the CCAAT-binding factor NF-Y, and this complex serves to up-regulate NF-Y target genes such as CCNA, CCNB, CDK1, CDC25C, and EFNB2 to promote cell cycle progression and chemoresistance following drug treatment (4,15). Surprisingly, wild-type p53 has been shown to interact with the same transcription factor NF-Y (16) and regulates many of the same target genes as described for mutant p53.…”
mentioning
confidence: 99%